2019
DOI: 10.1021/acsanm.9b00894
|View full text |Cite
|
Sign up to set email alerts
|

Flash Ablation of Tunable and Deep-Subwavelength Nanogap by Using a Spatially Modulated Femtosecond Laser Pulse for Plasmonic Application

Abstract: The fabrication of gold nanostructures on a dielectric substrate with a nanogap between the opposite tips is suitable for the excitation of hot spots. In this study, a novel and efficient one-step method is reported for fabricating a gold bowtie nanogap by using a spatially shaped femtosecond laser pulse. The size of the nanogap could be flexibly controlled by adjusting the pulse energy. The smallest nanogap produced by the proposed method measures 30 nm (≈1/26 of the laser wavelength). The formation mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…These nanovoids are an infinitesimal 3D space created within the clusters of AgNPs . Similar to hotspots created between the NPs and metal nano thin films or a 1D photonic crystal, the 3D space between two closely placed NPs providing nanogaps also experience augmented EM-field intensity. , Although previous experimentation and simulation studies using intermetallics such as titanium nanocomposites have shown very good correlation between Purcell factor (PF) and emission enhancements, the contribution from the nanovoids (within SCs) and cavity (infinitesimal volume between SCs and a thin silver film) environments have not been explored to date. In this context, we present a first time, direct correlation between the PF obtained from finite-difference time-domain (FDTD) simulations and emission enhancements from a radiating dipole placed in the cavity environment.…”
Section: Introductionmentioning
confidence: 99%
“…These nanovoids are an infinitesimal 3D space created within the clusters of AgNPs . Similar to hotspots created between the NPs and metal nano thin films or a 1D photonic crystal, the 3D space between two closely placed NPs providing nanogaps also experience augmented EM-field intensity. , Although previous experimentation and simulation studies using intermetallics such as titanium nanocomposites have shown very good correlation between Purcell factor (PF) and emission enhancements, the contribution from the nanovoids (within SCs) and cavity (infinitesimal volume between SCs and a thin silver film) environments have not been explored to date. In this context, we present a first time, direct correlation between the PF obtained from finite-difference time-domain (FDTD) simulations and emission enhancements from a radiating dipole placed in the cavity environment.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Using an objective lens with an NA of 0.45, Wang et al reported a novel method for high-resolution nanowire patterning through film ablation using a spatially shaped femtosecond laser pulse, which was formed by phase-based modulation. [30,31] The reported ultrafast pulsed laser ablation without requiring additional etching or transfer steps is a fast and cost-effective method to achieve controllable preparation of high-quality nanostructures. However, these techniques require tight focusing conditions to form a tiny spot with relatively short depth of focus, making it difficult to accomplish large-area fabrication on flexible substrates without an ultra-flat surface if a complex dynamic focusing unit is unavailable.…”
Section: Far-field Parallel Direct Writing Of Sub-diffraction-limit M...mentioning
confidence: 99%
“…In 2019, Xu et al used spatially shaped femtosecond laser pulses to fabricate gold bowtie nanostructures. By adjusting the pulse energy to control the size of the nanostructures, this method produced a minimum nanogap of 30 nm (the more 1/26 of the laser wavelength), which allows the patterning of large-area micro-nano structures on terahertz supersurfaces [47] (Figure 1I).…”
Section: Advances In Femtosecond Laser Preparation Of Precious Metal ...mentioning
confidence: 99%